Technical Guidance For Improving The Quality Of Private Skills And Training Institutions In Karanganyar Synergize, Innovate, And Accreditate - Ichwan Prastowo; Agung Wibiyanto (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2026)
The high labor force with limited job opportunities demands that Education and Training Institutions must be able to prepare a truly work-ready workforce that is able to answer future demands, for that reason the implementing team of this community service activity held technical guidance to improve quality so that it has accreditation recognized by the business world and industry. The Community Service activity aims to provide technical guidance in achieving institutional accreditation so that it is truly of good quality by providing knowledge and skills to participants, especially institutional administration in meeting 8 accreditation standard criteria. Unaccredited Job Training Institutions were recorded and given guidance on the use of accreditation that can improve national level quality which is useful in creating qualified students. The results obtained in this technical guidance were obtained as many as 35 active, official and licensed institutions from the Social and Manpower Office, only approximately 15 institutions have just been accredited, the enthusiasm of job training institutions in obtaining accreditation is very strong so that they follow the technical guidance seriously until the completion of this technical guidance implementation, not only here this guidance will continue to be provided by the implementing team until optimal results are truly obtained.